A new species of Cosmetus (Opiliones, Cosmetidae) from the Colombian pacific region - Betancourt-Caicedo, Alejandro; Medrano, Miguel (Zootaxa, 2025)
Cosmetus Perty, 1833 is a cosmetid genus with 21 species described which can be recognized by its characteristic fused spine in area III, although this character is presumably homoplastic. In this paper we describe one new species of the genus sensu lato from the Colombian pacific region based on genital morphology and external characters. Cosmetus calima sp. nov. (type locality: Valle del Cauca, Buenaventura, Bajo Calima) can be distinguished by the combination of the following features: dorsal scutum uniformly yellow without paired depigmented spots; spine undivided, shorter than dorsal scutum and not projecting backwards; femur IV long and unarmed; smooth tarsal claws III and IV; male without hypertelic chelicerae, with five basitarsomeres I and penis with a medial basal swelling on the dorsal region of the ventral plate that touches the gland. It is similar to Cosmetus acanti and Cosmetus balboa, which also inhabit the Chocó-Darién moist forests, differing subtly from them in its coloration and spot pattern, the length and inclination of spine in area III, the shape of ventral plate of penis and the position of MS D and MS E.